Transient multiple neonatal onychodystrophy. Case report and review of the literature. - Rodriguez-Lechtig, B.; Jaramillo Arboleda, A.; Sanchez-Zapata, M.J.; Orduz-Robledo, M.; Estupiñan, M.C.; Motta , A. (European Journal of Pediatric Dermatology, 2025)
Neonatal onychodystrophy is a rare condition, usually associated with congenital candidiasis. We report a case of severe dystrophy of multiple nails in a newborn, which resolves spontaneously in a few months. The pregnancy history did not show any noteworthy problems. The perinatal history showed prolonged dystocic labor, clavicle fracture and jaundice due to blood group incompatibility. The negativity of the mycological examination, the absence of significant causal factors and the rapid spontaneous resolution, despite the apparent severity of the clinical picture, make this case unique and we propose the name of transient multiple neonatal onychodystrophy (TMNO). All the articles in the literature related to this condition are reviewed.